Health Performance of the Districts in India: An Empirical Analysis of NFHS-5 Data - Pal, Manoranjan; Pandey, Ravi; Bharati, Premananda; Bharati, Susmita (International Journal of Statistical Sciences, 2023)
Development and health, specifically child health, can be multi-dimensional and need to be investigated more deeply specially in a developing nation like India. This paper tries to find out the best and the worst performing districts using NFHS-5 district level percentage figures. First, some groups of variables named ‘development’, ‘health’ and ‘health behavior’ were created by taking similar types of variables relevant for the group and then the variables within each group were combined through principal component analysis. The districts were ranked according to the performance of each group and then these ranks were combined to get the overall rank to choose the best and the worst performing districts. We see that among top ten best performing districts, five are from Tamil Nadu, four are from Kerala and one is from Punjab, whereas most of the ten worst performing districts are from Jharkhand and Bihar and the rest are from UP, Assam and Meghalaya. Since another objective of the paper is to find the variables related to the child health scores, this variable was regressed on scores of other groups along with state dummies. Surprisingly all the variables relating to mothers like mother’s health and health facilities, health behaviour, mother being not underweight and mother being not anemic turned out to have significant positive effect on child health. Thus, mothers are the key factor towards the good health of children, and it is the mothers who should be given maximum attention to. International Journal of Statistical Sciences, Vol. 23(2), November, 2023, pp 75-86